Development and movement of a mid-tropospheric Cyclone in the westerlies over India (MAUSAM, 1981)
The effect of a developing upper tropospheric ridge in the westerlies on the trough ahead has been studied. It has been shown that growth of an upstream ridge is one of the important factors for the development of the downstream trough, and if the ridge continues to build up, the  trough, inspite of the formation of a cut off low in it, continues to deepen and so does the cut off low which can become a deep cyclone showing SE'ly movement as envisaged by Bjerknes ( 1951).